Oxidative stress as a signal to up-regulate gamma-cystathionase in the fetal-to-neonatal transition in rats - Martín, J.A.; Pereda, J.; Martínez-López, I.; Escrig, R.; Miralles, V.; Pallardó, F.V.; Viña, J. R.; Vento, M.; Viña, J.; Sastre, J. (Cellular and Molecular Biology, 2007)
Hepatic gamma-cystathionase, a rate-limiting enzyme for the synthesis of L-cysteine from L-methionine in the trans-sulphuration pathway, exhibits significantly higher activity in the newly born infant as compared to the fetus. The aim of this work was: 1) To determine whether the increase in gamma-cystathionase activity occurring in the fetal-to-neonatal transition is due to up-regulation of its mRNA and protein, 2) To elucidate the mechanisms responsible for this increase in gamma-cystathionase activity. Our results show that expression of gamma-cystathionase at both the mRNA and protein levels was higher in newborn than in fetal liver. gamma-Cystathionase activity in fetal hepatocytes in vitro increased when incubated with tert-butyl-hydroperoxide at low concentration (0.01 mM). Hence, moderate oxidative stress would act as a signal to up-regulate gamma-cystathionase in the fetal to neonatal transition. Stress hormones, such as phenylephrine or glucagon also increased gamma-cystathionase activity in fetal hepatocytes. We also report a competitive inhibition of purified gamma-cystathionase by L-cysteine, which would help to maintain physiological low L-cysteine levels in hepatocytes. In conclusion, our results show that increased hepatic gamma-cystathionase activity in the fetal-to-neonatal transition is due to up-regulation of its gene expression mediated by stress hormones together with the physiological oxidative stress that occurs at birth.